Zero‐inflated prediction model in software‐fault data. Issue 1 (1st February 2016) - Fagundes, Roberta A.A.; Souza, Renata M.C.R.; Cysneiros, Francisco J.A.
Abstract : Software fault data with many zeroes in addition to large non‐zero values are common in the software estimation area. A two‐component prediction approach that provides a robust way to predict this type of data is introduced in this study. This approach allows to combine parametric and non‐parametric models to improve the prediction accuracy. This way provides a more flexible structure to understand data. To show the usefulness of the proposed approach, experiments using eight projects from the NASA repository are considered. In addition, this method is compared with methods from the machine learning and statistical literature. The performance of the methods is measured by the prediction accuracy that is assessed based on the mean magnitude of relative errors.